2018
DOI: 10.1029/2017ms001250
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Coupled Model of Atmosphere, Ocean Physics, and Ocean Biogeochemistry to Represent Biogeophysical Feedback Effects in the Tropical Pacific

Abstract: Multiple processes are involved in modulating the El Niño‐Southern Oscillation (ENSO) in the tropical Pacific, and these processes are neither well‐represented nor well‐understood in climate models. A new hybrid coupled model (HCM) of atmosphere, ocean physics, and ocean biogeochemistry (AOPB) is developed to represent the feedback from ocean biogeochemistry onto ocean physics via modulating the penetration of shortwave radiation in the upper ocean. An ocean biogeochemistry model is coupled with a simplified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…For example, the amplitude of ENSO is decreased when biological feedback is included, whereas it can be increased in other studies (summarized in Park, Kug, & Park, ). On ENSO scale, it is demonstrated that large‐scale biophysical interactions acted to have a negative feedback on ENSO (Zhang et al, ). This is completely different from our current results, in which the Chl TIW effect acts to increase ENSO amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the amplitude of ENSO is decreased when biological feedback is included, whereas it can be increased in other studies (summarized in Park, Kug, & Park, ). On ENSO scale, it is demonstrated that large‐scale biophysical interactions acted to have a negative feedback on ENSO (Zhang et al, ). This is completely different from our current results, in which the Chl TIW effect acts to increase ENSO amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…• Supporting Information S1 atmosphere interaction (Gnanadesikan et al, 2010;Jochum et al, 2010;Kim et al, 2018;Lengaigne et al, 2007;Murtugudde et al, 2002;Nakamoto et al, 2001;Park, Kug, Seo, et al, 2014;Sweeney et al, 2005;Timmermann & Jin, 2002;Wetzel et al, 2006;). On interannual timescale, for example, Zhang et al (2018a) argued that interannual variability of chlorophyll can induce a negative feedback onto ENSO; that is, interannually varying chlorophyll effect acts to reduce ENSO amplitudes.…”
Section: 1029/2018gl081275mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies documented basic performances of the coupled ocean physics‐biogeochemistry model, which shown that the model could well simulate mean state, seasonal cycle, and interannual variability in the physical and biological fields (Tian et al, ; Wang et al, , ; Zhang et al, ). Figure shows the response of chlorophyll to ENSO for the observations and model forced by observed and reanalysis atmospheric forcing.…”
Section: Overview Of the Model Simulationsmentioning
confidence: 99%
“…However, how these processes interact with one another is an ongoing issue of debate. Particularly, ENSO can induce large variations in freshwater flux (FWF) at the sea surface and ocean chlorophyll, both of which can induce feedback onto ENSO (Huang et al, ; Maes et al, ; Murtugudde & Busalacchi, ; Timmermann, 2002; Vialard & Delecluse, ; Wu et al, ; Zhang, Busalacchi, et al, , Zhang et al, , Zhang et al, , Zhang et al, ; Zhang & Busalacchi, ; Zhi, Zhang, Lin, & Shi et al, ; Zhi, Zhang, Lin, & Yu, et al, ), but the interactions between these two processes remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%